High damping and nonlinear vibration of sandwich beams with entangled cross-linked fibres as core material. (1st July 2019) - Piollet, Elsa; Fotsing, Edith Roland; Ross, Annie; Michon, Guilhem
Abstract: This article investigates the use of a recently developed fibrous core material to increase vibration damping in sandwich beams. The entangled cross-linked fibre (ECF) material is made of short carbon fibres cross-linked with epoxy resin. Dry friction between fibres provides energy dissipation when the material is deformed. Previous measurements on the material are post-processed to provide a simplified viscoelastic description of the material, for an easier interpretation of subsequent structural testings. Two sandwich beams are compared with reference honeycomb beams: a sandwich beam with an ECF core, and a hybrid beam with a honeycomb core and an ECF insert. Steady-state tests are performed on both types of beams to obtain their frequency responses for different excitation levels, and the corresponding apparent loss factors are computed. The beam with a full ECF core shows an apparent loss factor more than ten timess higher than the reference honeycomb beam. The hybrid sandwich beam provides an apparent loss factor four times higher than the reference honeycomb beam. All beams exhibit nonlinear softening responses consistent with a dry friction phenomenon in the material: the resonance frequencies decrease with increasing excitation amplitude, and damping increases then decreases again at very high amplitudes while remaining largely superior to that of the honeycomb beams. Transient impact testings are also presented for a qualitative comparison of the ECF and reference beams, and the ECF beams lead to shorter decay times compared to the reference beams.